Longitudinal association between trust, psychological symptoms and community engagement in resettled refugees. Issue 10 (30th August 2018) - Nickerson, Angela; Liddell, Belinda J.; Keegan, David; Edwards, Ben; Felmingham, Kim L.; Forbes, David; Hadzi-Pavlovic, Dusan; McFarlane, Alexander C.; O'Donnell, Meaghan; Silove, Derrick; Steel, Zachary; van Hooff, Miranda; et al.
Abstract: Background: The mental health and social functioning of millions of forcibly displaced individuals worldwide represents a key public health priority for host governments. This is the first longitudinal study with a representative sample to examine the impact of interpersonal trust and psychological symptoms on community engagement in refugees. Methods: Participants were 1894 resettled refugees, assessed within 6 months of receiving a permanent visa in Australia, and again 2–3 years later. Variables measured included post-traumatic stress disorder symptoms, depression/anxiety symptoms, interpersonal trust and engagement with refugees' own and other communities. Results: A multilevel path analysis was conducted, with the final model evidencing good fit (Comparative Fit Index = 0.97, Tucker–Lewis Index = 0.89, Root Mean Square Error of Approximation = 0.05, Standardized Root-Mean-Square-Residual = 0.05). Findings revealed that high levels of depression symptoms were associated with lower subsequent engagement with refugees' own communities. In contrast, low levels of interpersonal trust were associated with lower engagement with the host community over the same timeframe. Conclusions: Findings point to differential pathways to social engagement in the medium-term post-resettlement. Results indicate that depression symptoms are linked to reduced engagement with one's own community, while interpersonal trust is implicated in engagement with the broader community in the host country. These findings have potentially important implications for policy and clinical practice, suggesting that clinical and support services should target psychological symptoms and interpersonal processes when fostering positive adaptation in resettled refugees.